2017
DOI: 10.1158/1538-7445.am2017-5199
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5199: Preclinical activity of the FGFR2-targeted thorium-227 conjugate in preclinical models of colorectal, gastric and triple-negative breast cancer

Abstract: FGFR2 is a transmembrane tyrosine kinase receptor, consisting of three extracellular N-terminal immunoglobulin-like domains which are involved in ligand-binding as well as in receptor dimerization. Ligand-independent activation of FGFR2 signaling either via genomic amplification, gene fusion events, mRNA overexpression, or mutations has been observed e.g. in gastric cancer, colorectal cancer (CRC), and triple-negative breast cancer (TNBC). As such, FGFR2 has been described to be involved in cancer progression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…FGFR2-TTC reduced the viability of FGFR2-expressing cells, resulting in accumulation of DNA DSBs and cell cycle arrest in the G2/M phase (Table 1). 77 In a preclinical murine model of human gastric cancer, whole-body autoradiography visualized the FGFR2-TTC tumor uptake in mice bearing subcutaneous xenografts. 77 Furthermore, treatment with a single dose of 500 kBq/kg specifically reduced the tumor growth in human colorectal, gastric cancer, and TNBC xenograft mouse models (Table 1).…”
Section: Cd70-ttcmentioning
confidence: 99%
See 1 more Smart Citation
“…FGFR2-TTC reduced the viability of FGFR2-expressing cells, resulting in accumulation of DNA DSBs and cell cycle arrest in the G2/M phase (Table 1). 77 In a preclinical murine model of human gastric cancer, whole-body autoradiography visualized the FGFR2-TTC tumor uptake in mice bearing subcutaneous xenografts. 77 Furthermore, treatment with a single dose of 500 kBq/kg specifically reduced the tumor growth in human colorectal, gastric cancer, and TNBC xenograft mouse models (Table 1).…”
Section: Cd70-ttcmentioning
confidence: 99%
“…77 FGFR2-TTC was well tolerated, with no significant body weight loss observed in any of the xenograft models tested. 77…”
Section: Cd70-ttcmentioning
confidence: 99%
“…Further, as thorium-227 is the progenitor of radium-223, the supply chain is established through Xofigo®. We have previously demonstrated that TTCs induce γ-H2A.X and G2/M cell cycle arrest in various cancer models indicating the involvement of DNA damage response [6,10]. Furthermore, the inhibition of multiple pathways of DNA repair has been described in the literature to have a radiosensitizing effect [16][17][18].…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, thorium-227 (half-life of 18.7 days), the parental radionuclide of radium-223, can be complexed to several chelator families including those of the 3,2-hydroxypyridinone (3,2-HOPO) class [5]. We have previously reported on several examples of targeted thorium-227 conjugates (TTCs) targeting a multitude of tumor-associated antigens including the HER2-TTC [6][7][8][9][10]. Human epidermal growth factor receptor 2 (HER2) is a transmembrane tyrosine kinase receptor that is part of the human epidermal growth factor receptor (EGFR) family [11].…”
Section: Introductionmentioning
confidence: 99%
“…227 Th has been successfully labeled to a number of such antibodies. [7][8][9][10][11][12][13][14] However, 223 Ra does not easily form stable complexes. 15 Therefore, it is possible that after the decay of 227 Th to 223 Ra, 223 Ra may dissociate from the antibody complex, resulting in free 223 Ra ions with a biodistribution independent of the 227 Th-labeled antibody.…”
Section: Introductionmentioning
confidence: 99%